2013
DOI: 10.4137/ccrep.s10200
|View full text |Cite
|
Sign up to set email alerts
|

Balloon Dilation in Sporadic Inclusion Body Myositis Patients with Dysphagia

Abstract: Here, we describe balloon catheter dilation at the upper esophageal sphincter (UES) in three sporadic inclusion body myositis (s-IBM) patients with dysphagia. Initially, we performed IVIg therapy, and, three months later, switched to balloon dilation therapy. A 12-Fr balloon catheter was inserted from the mouth under fluoroscopy and the balloon inflated at the UES. The catheter was pulled back and re-inserted several times. We examined videofluoroscopy (VF) and pressure at the oropharynx, hypopharynx and UES u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 15 publications
(20 reference statements)
1
27
0
4
Order By: Relevance
“…[65] Caution is suggested in recommending cricopharyngeal myotomy as there is a report of worsening after that procedure in a patient who also had a hiatal hernia. [66]…”
Section: Therapymentioning
confidence: 99%
“…[65] Caution is suggested in recommending cricopharyngeal myotomy as there is a report of worsening after that procedure in a patient who also had a hiatal hernia. [66]…”
Section: Therapymentioning
confidence: 99%
“…Major side effects of alemtuzumab are the development of an autoimmune thyroiditis or idiopathic thrombocytopenic purpura . In three controlled prospective studies with IVIG, no increase of the limb strength could be observed , whereas the dysphagia was improved significantly .…”
Section: Introductionmentioning
confidence: 99%
“…Other uncontrolled studies, each with a small number of patients, addressed the effect of the following interventions in IBM: cricopharyngeal myotomy, pharyngoesophageal dilatation, percutaneous endoscopic gastrostomy (PEG) and injection of botulinum toxin. A benefit was shown for both myotomy and dilatation, but the results were limited by the number of only 10 patients . So far, treatment with botulinum toxin has shown different results, ranging between no effect and improvement in swallowing for several months .…”
Section: Introductionmentioning
confidence: 99%
“…In controlled prospective studies, IVIG had improved dysphagia [ 45,46,47] , but had no impact in increasing of the limb strength [47][48][49][50].…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%